2019
DOI: 10.17533/udea.mut.v12n2a05
|View full text |Cite
|
Sign up to set email alerts
|

Iranian Amateur Subtitling Apparatus: A Qualitative Investigation

Abstract: The number of studies addressing non-professional or amateur subtitling or fansubbing has increasingly multiplied over the past years, underlying its relevance in the present world. This is partly because a growing number of audiences worldwide now watch TV series and films with subtitles by amateur subtitlers, which are freely shared online, and Iranian viewers are certainly included. In Iran, to get around the “cultural gate-keeping” policy advocated and strictly enforced by the state in the national media s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…These findings differ from those of fansubbing and scanlation communities (Ameri and Khoshsaligheh, 2019; Valero-Porras and Cassany, 2016; Zhang and Cassany, 2016), in which the roles of the fan translators were typically hierarchical and narrowly-focused on a specific task. The fansubbers were able to correct each other, but due to the hierarchy, there were rarely discussions between them.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These findings differ from those of fansubbing and scanlation communities (Ameri and Khoshsaligheh, 2019; Valero-Porras and Cassany, 2016; Zhang and Cassany, 2016), in which the roles of the fan translators were typically hierarchical and narrowly-focused on a specific task. The fansubbers were able to correct each other, but due to the hierarchy, there were rarely discussions between them.…”
Section: Discussioncontrasting
confidence: 75%
“…The organization during fan translation in various studies has been identified as being hierarchical and distributed-every participant having certain ascribed roles (i.e., transcriber, translator or editor) and certain workloads with high commitment and quality standards (Ameri and Khoshsaligheh, 2019;Aragão, 2016;D ıaz-Cintas and Muñoz Sa´nchez, 2006;Saadat, 2017;Valero-Porras and Cassany, 2016;Zhang and Cassany, 2016). The learning in these communities was rarely described through mentorship or feedback, but more so through individual practices of sophisticated audio-visual comprehension in case of fansubbing (Liu and de Seta, 2014;Zhang and Cassany, 2019) or reading comprehension development through multimodal cues in case of scanlation (Valero-Porras and Cassany, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this shortcoming, no remuneration, little or no training, no respect for the standards of professional practice and copyright infringement have been the noted hallmarks of non-professional subtitling (Antonini, Cirillo, Rossato, & Torresi, 2017). The definition made by Antonini et al (2017), to some extent, matches the Iranian cases; however, Ameri and Khoshsaligheh (2019) report that Iranian non-professional subtitlers are, at times, translation students or graduates and they are paid-although substantially little-for their work by the piracy film websites. Additionally, their work is not supervised by any Iranian authorities, as this is an underground and unauthorized activity, aiming to "circumvent windowed release strategies and other forms of geoblocking" (Dwyer, 2019: 441).…”
Section: Non-professional/amateur Subtitlingmentioning
confidence: 99%
“…However, these conflicting findings can be justified by the fact that Iran is not a subtitling country and official subtitling for fiction content is almost non-existent, and aside from the exposure of the younger generation to subtitling, the Iranian audiences are not typically accustomed to reading subtitles and may prefer the convenience of listening to dubbed versions. Also, what is watched by the Iranians is the product of amateur subtitlers who are not obliged to comply with the subtitling standards (Ameri & Khoshsaligheh, 2019). Yet, this should be stressed that the members of this community appeared not to be lay viewers as they do not simply watch the programs for the sake of sheer passing of time but they usually critically consider the program from varied perspectives.…”
Section: Subtitlingmentioning
confidence: 99%